Liability issues with Artificial Intelligence in the national and international context - Rautanen, Ville (My University, 2020)
The pro gradu -thesis discusses the liability issues regarding Artificial Intelligence (AI) applications, especially liability of robots and other autonomous machines, and it provides an answer to the question “Who is liable when AI makes a mistake?” This problem is looked first from the national and more individual perspective and then from an international perspective regarding the state’s responsibility and jurisdiction. The main issue can is that if, for example, a self-driving car collides with another vehicle, who then can be held liable as instead of a human, the car was driven by an algorithm. As there is no human driver, the responsible party needs to be found somewhere else, and it could be the owner or the manufacturer of the car, the software designer or at some point maybe even the AI itself. Also, no one can be blamed without reasons or applicable law, so there is a need for suitable reasoning to hold the party liable, and the legislations need to be updated to recognise the liable party regarding the new technology. These same aspects are also examined by the point of view of international law and treaties, especially regarding state jurisdiction and responsibility. The research method of this study is a qualitative and a bit legal dogmatic method. My primary sources are different articles and reports on AI liability and various international books from important international law authors as well as publications from international organisations. Also, different national and international guidelines and legislation have an integral part in regulating AI, and therefore they are also utilised and analysed. The findings of this research are that there is not just one and simple answer to the questions about the liable party, and the liable person depends greatly on the situation. The manufacturer could often be held strictly liable for any damage caused by the AI product. In addition, the owner of the product could be held liable in the same way as the owner of the animal and in the future robots could get personhood similar to the personhood of the companies, which would make the robot liable for itself. However, the legislation in this area is a bit behind from the technological development internationally and nationally. That means that the law needs to catch up with the technical development so victims can get compensated by the right liable party.

Tutkielma käsittelee tekoälyä koskevia vastuukysymyksiä, liittyen erityisesti robotteihin ja muihin autonomisiin koneisiin. Tutkielma myös pyrkii vastaamaan kysymykseen ”Kuka on vastuussa, kun tekoäly tekee virheen?” Tätä kysymystä ja koko vastuuongelmaa tarkastellaan kansallisesta ja yksilöllisestä näkökulmasta sekä kansainvälisestä näkökulmasta. Pääkysymys on, että jos esimerkiksi itse ajava auto törmää toiseen ajoneuvoon, kuka on vastuussa, koska ihmisen sijaan algoritmi ajoi autoa. Koska kuljettajaa ei ole, joku muu on vastuussa oleva henkilö, joka voi olla auton omistaja tai valmistaja, ohjelmistosuunnittelija tai jopa tekoäly itse. Ketään myöskään ei voida syyttää ilman aihetta tai sovellettavaa lakia, joten vastuunalaisen henkilön löytämiseksi on oltava asianmukaiset perustelut. Myös lakien täytyy olla ajan tasalla koskien uutta teknologiaa ja siihen liittyviä vastuukysymyksiä. Näitä samoja asioita tarkastellaan myös kansainvälisen oikeuden ja sopimusten näkökulmasta, erityisesti valtioiden lainkäyttövallan ja vastuun osalta. Tutkielman metodi on laadullinen sekä osittain myös oikeusdogmaattinen. Ensisijaisina lähteinä ovat erilaiset artikkelit ja raportit tekoälyn vastuusta, kansainvälisen oikeuden kirjoitukset tärkeiltä kansainvälisen oikeuden kirjoittajilta sekä kansainvälisten järjestöjen julkaisut. Eri kansallisilla ja kansainvälisillä ohjeistuksilla ja lainsäädännöllä on myös olennainen osa tekoälyn sääntelyssä, ja siksi tutkielma tutkii myös niitä. Tutkielman johtopäätöksenä on, että vastuunalaista henkilöä koskeviin kysymyksiin ei ole vain yhtä vastausta, ja tilanteesta riippuu, kuka on vastuussa. Valmistaja on usein ankarasti vastuussa robotin aiheuttamista vahingoista. Lisäksi tuotteen omistaja voi olla mahdollista saattaa vastuuseen kuten eläimen omistaja ja tulevaisuudessa robotit voisivat saada oikeushenkilön kaltaisen henkilöllisyyden, jolloin robotti voisi olla itse vastuussa. Lainsäädäntö on kuitenkin jäljessä tekniikan kehityksestä niin kansainvälisesti kuin kansallisesti tekoälyn suhteen. Lain tulisi pysyä tekniikan kehityksen mukana, jotta vastuussa oleva henkilö voidaan löytää ja vahingonkärsijä saa korvauksensa.
Keywords: International Law, tort law, Artificial Intelligence, robots, liability, state responsibility